Thermomagnetic characterization of organic-based ferrofluids prepared with Ni ferrite nanoparticles - Arana, Mercedes (2017)
In this work, a thermomagnetic characterization of kerosene-based ferrofluids (FFs) prepared with Ni-ferrite nanoparticles (NPs) is performed by measuring their thermal conductivity and diffusivity coefficient enhancements. The particles were synthesized by high-energy ball milling, as an alternative to the most commonly chosen NPs synthesis methods for FFs. The action of an applied magnetic field on the FF increases the thermal conductivity and diffusivity due to cooperation between the NPs, as it agglomerates them favoring chain-like and clusters formations. It was found that the heat capacity of the studied FFs decreases under the application of a magnetic field. The obtained results for thermal conductivity of FFs under magnetic fields were fitted by a gas-compression model that considers NPs agglomerates in the fluid.